Investigation of carbon-nanotube based passive mode-locked fiber lasers - Jiang, Kai (2010)
This report documents the investigation and construction of a passively mode-locked fiber laser based on carbon nanotube as saturable absorber. Passive mode-locking can generate ultra-short optical pulses with fs~ps pulse width. It addition, multiple solitons can be generated in order to increase the repetition rate of pulse trains when a passively mode-locked fiber laser operates under strong pumping. Hence, the investigation on the passively mode-locked fiber laser is of strong motivation. Various passive mode-locking techniques, such as nonlinear loop mirror (NOLM), nonlinear polarization rotation (NPR), and semiconductor saturable absorber mirrors (SESAM) have been successfully demonstrated before. However, these techniques have some drawbacks. In this report, an all-fiber ring laser incorporating with single wall carbon nanotube was constructed and investigated. By adjusting the polarization controller, a self-started stable fundamental mode- locking with a 4.79MHz repetition rate was achieved at normal cavity dispersion regime. Then the fiber laser system was modified in order to get anomalous cavity dispersion. The fiber laser generates solitons when it is mode-locked at 18.71 MHz repetition rate with input pumping power of 12 mW. The dynamics of the number of solitons was demonstrated by increasing pump power. The passively mode-locked fiber laser can generate multiple solitons from 1 to 10 when the pump power was increased from 12mW to 60mW. Later we modified the experiment setup, a wavelength-switchable passively harmonically mode-locked fiber laser with low pumping threshold was obtained. When the pumping power of 980nm laser diode was 60 mW, the fiber laser was passively mode-locked at either the 23rd harmonic at 1530 nm or the 13th harmonic at 1554 nm by setting different polarization in the cavity, respectively. The measured super mode suppression ratio of each wavelength was more than 30 dB. The pulses at 1530 nm were characterized with a repetition rate of 328.44 MHz, a transform-limited pulse width of 1.3 ps, and a timing jitter of 142.6 fs.